2015
DOI: 10.1186/s12959-015-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of non-vitamin K antagonist oral anticoagulants in daily practice: the need for comprehensive education for professionals and patients

Abstract: Non-vitamin K antagonist oral anticoagulants (NOACs) are increasingly used for the prevention and treatment of venous thromboembolism and for stroke prevention in patients with atrial fibrillation. NOACs do not require routine coagulation monitoring, creating a challenge to established systems for patient follow-up based on regular blood tests. Healthcare professionals (HCPs) are required to cope with a mixture of patients receiving either a vitamin K antagonist or a NOAC for the same indications, and both pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 19 publications
0
37
0
1
Order By: Relevance
“…In order to minimize the risk of serious bleeding, we initiate the oral anticoagulation regimen – VKA or NOAC – after the EPW have been taken out. Although none of the eight patients were on NOACs, we believe that it is prudent to commence these regimens after pulling out the EPW, as no standard screening for NOACs is routinely used [14]. On the other hand, patients who have a strong indication for DAPT, for example by coronary intervention with drug eluting stent implantation in the short-time perioperative period, still have their EPW removed under this medication.…”
Section: Discussionmentioning
confidence: 99%
“…In order to minimize the risk of serious bleeding, we initiate the oral anticoagulation regimen – VKA or NOAC – after the EPW have been taken out. Although none of the eight patients were on NOACs, we believe that it is prudent to commence these regimens after pulling out the EPW, as no standard screening for NOACs is routinely used [14]. On the other hand, patients who have a strong indication for DAPT, for example by coronary intervention with drug eluting stent implantation in the short-time perioperative period, still have their EPW removed under this medication.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that plasma drug levels will be available within the approved time frame for thrombolysis so for FXa inhibitors, judgement relies on timing of most recent dose together with patient characteristics; in the absence of available evidence, it has been suggested that thrombolytic therapy not be given within 24-48 hours following last NOAC dose. 82 …”
Section: Thrombolysis In Ischaemic Strokementioning
confidence: 99%
“…In renal impairment, apixaban is currently preferred, with the lower dose of 2.5 mg BID recommended in case of creatinine >133 mmol/L, elderly patients (>80 yrs) and small weight (<60 kg) (59). Finally, renal patients are subjected to the most severe complications of drug interactions, which tend to be increasingly identified (8).…”
Section: Oral Anticoagulation and Renal Impairmentmentioning
confidence: 99%
“…DOACs are gaining new indications, rivaroxaban for prevention of atherothrombosis in coronary artery disease, and several DOACs are being considered in cancer patients as well (5)(6)(7). While the use of DOACs is increasing, clinicians will encounter many patients switching from traditional vitamin K antagonists (VKAs) to DOACs, and broad education is required (8). To respond to the challenge of increased repertoire of anticoagulants in patients with risk factors for both thrombosis and bleeding, e.g., elderly patients undergoing vascular surgery, a special anticoagulation clinic was launched in conjunction with the Coagulation Disorders Unit in 2015.…”
Section: Introductionmentioning
confidence: 99%